EKSPLORASI TERHADAP KEMUNGKINAN DESAIN PODCAST PENDIDIKAN TINGGI DI INDONESIA - Rintis Mulyani (Fakultas Dakwah dan Komunikasi, 2021)
This study aims to explore the possibilities of podcast designs that can be applied by higher education institutions in Indonesia. Podcast media has benefits in distance learning. However, there is no higher education in Indonesia that uses podcasts to deliver learning material. Therefore, this research synthesizes several models of podcasts that can be mixed and matched by teachers in creating learning podcasts. This article reviews Interest-Driven Learning Design, podcast types, and podcast types. IDLD reviews learning that accommodates students' interests outside the context of the educational environment; the types and types of podcasts review podcast characteristics that can be used as a guide when creating learning content through podcasts